Evaluasi Sifat Anti Parasit Terhadap Daun Mayana (Solenostemon scutellarioides. L) - Elni Elni; Irine Ike Praptiwi; Maria M. N. N. Lesik (Faculty of Agriculture, Musamus University, 2020)
Animal diseases that are quite detrimental are worm parasitic diseases, so there is a need for herbal treatments. One of the natural ingredients used as an anthelmintic is Mayana Leaves (Solenostemon scutellarioides (L)). Mayana leaves (Solenostemon scutellarioides (L)) also contain tannins. In the past few years, there have been developments related to the use of tannins as an anti-melting agent. This study is to determine the extent of Mayana leaf's ability (Solenostemon scutellarioides (L)) which is used as an anti-parasitic treatment in livestock. The data processing and analysis techniques used in this study are historical methods using primary and secondary sources as the object of research and testing of mayana leaf tannin (Solenostemon scutellarioides, L.). The variable observed is anthelmintic. Mayana leaves (Solenostemon scutellarioides, L.) contain tannins, saponins, steroids, terpenoids, flavonoids and essential oils. The ability of tannins Mayana leaves (Solenostemon scutellarioides, L.) can inhibit the growth of microorganisms or enzyme activity and damage the membrane. Worm membranes are damaged because tannins cause paralytic worms that eventually die. Giving Mayana leaves (Solenostemon scutellarioides, L.) with 1.19% tannin content can be used as an anthelmintic for worm parasites